Measuring Potential Effect on Bank Stability After Muhammadiyah Makes Bank Run - Desi Trisnawati; Rosana Eri Puspita; Mohammed Asmy bin Mohd Thas Thaker; Anwar Radiamoda (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Muhammadiyah, a major Indonesian community organization, plans to withdraw approximately 13 trillion rupiah from Bank Syariah Indonesia (BSI) due to concerns over financial concentration risks. Beyond its tangible assets, Muhammadiyah’s influence over its followers raises the potential for a bank run, threatening banking stability. This study aims to analyze netizen behavior toward Muhammadiyah’s decision and the likelihood of its followers following suit. Employing a qualitative netnography approach, data were collected from 2,402 YouTube comments using Nawala software and analyzed with NVIVO. Findings reveal that netizens extensively discussed trust in government, development plans, deposit safety, and fund allocation, with predominantly negative sentiments. Approximately 65–70% expressed distrust in the government, 85% questioned BSI’s fund allocation, and 55–60% supported Muhammadiyah’s proposal to establish a new bank. Strong public support for Muhammadiyah’s actions indicates a risk of a broader bank run. The study concludes that public distrust in the government and BSI, amplified by Muhammadiyah’s influence, poses a threat to financial stability. Transparent communication and robust deposit guarantees by the government and BSI are essential to mitigate further crises.